Folk Narratives in the Modern Era: Adaptation, Transformation, and Continuity - Shivaji Rama Gudaji (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Myths, legends, folktales, proverbs, riddles, and ballads are all examples of folk narratives that have long served as important reservoirs of cultural memory, social values, and community identity. These stories come from oral tradition and contain the moral values, common imagination, and historical experiences of groups of people. With the rise of modernity, including industrialisation, urbanisation, globalisation, widespread literacy, mass media, and digital technologies, folk literature has evolved a lot in both its form and its purpose. This study analyses the adaptation of folk narratives to contemporary contexts while maintaining their traditional structures, exploring the balance between preservation and innovation in narrative practices. The study takes an interdisciplinary approach by combining folklore studies, cultural anthropology, and postcolonial literary theory. It looks at how old stories are told in new ways, as in books, movies, TV series, and digital media. The analysis demonstrates that contemporary influences may alter the narrative style and content of stories, although they do not affect the fundamental moral and cultural essence of these narratives. Folk literature continues to function as a vehicle for social education, moral reflection, and artistic engagement, while also addressing contemporary socioeconomic realities. Modernity has transformed the way people tell and talk about traditional stories. In the past, oral storytelling relied on live performances and group participation; presently, it can be found in books, videos, animations, and on the internet. These modifications preserve the fundamental ideas, moral lessons, and creative patterns, but they also add modern topics like gender equality, caring for the environment, social justice, and political critique. Adaptations of Indian folktales, like Tenali Raman or regional tribal legends, use new episodic structures and character development to show how folk stories may be relevant to modern issues while still being interesting. The study emphasises the role of folk literature as a means for social critique. Modern adaptations combine humour, satire, and allegory from ancient genres to talk about big social issues including corruption, caste and class hierarchies, and destruction to the environment. Digital technologies and social media make storytelling even more democratic by helping communities keep, change, and share their stories with more people. The mix of old and new technologies and folk customs makes cultural exchange, audience participation, and interactive creation better. This keeps folk literature alive. In short, the research shows how folk stories are still important today and how they can change and adapt throughout time. Modern influences impact how stories are told, how they are passed down, and what subjects they deal with. However, they also make folk literature richer by offering individuals methods to talk about their culture, reflect about morals, and comment on society. The interplay between adaptation and continuity illustrates that folk literature endures as a vibrant cultural practice, proficient in harmonising tradition and modernity, safeguarding social identity, and cultivating moral imagination in a rapidly evolving context.